RaiseMeUp : Inovasi Platform Donasi C2C untuk Kreator Independen di Era Ekonomi Digital - Febryan Dwi Siswanto; Yanwari Rahmad Mujianto; Faiq Fajar Satritama; Gunawan Prasetya Jati (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
The development of the digital economy has created a new ecosystem for independent creators to obtain more independent and sustainable sources of income. Amid the increasing need for direct support from fans, the RaiseMeUp platform was developed as a Consumer-to-Consumer (C2C) donation solution that enables seamless interaction between creators and their supporters. This research aims to design and build a digital donation platform that is user-friendly, secure, and able to increase creator engagement and independence in managing profiles, content, and income transparently. The system development method used in this research is the Waterfall method, which consists of five main stages: system requirements analysis, software design, implementation, testing, and evaluation. In system development, Laravel technology is used as a backend framework, MySQL as a database management system, and Tailwind CSS to design an intuitive and responsive user interface. Key features implemented include OTP verification for security, a user role system (admin, creator, and supporter), and integration with the Midtrans payment gateway for fast and secure donation transactions. Test results show that the RaiseMeUp platform functions optimally in supporting creators in receiving direct donations, managing interactions, and providing control over their content and profiles. Evaluations were also conducted to assess functionality and user satisfaction, which showed positive results and validated the system's design and implementation. This research provides a significant contribution to the development of donation-based digital platforms in Indonesia and opens up opportunities for further development, such as analytics features, real-time notifications, and content personalization to increase user engagement in the future.